Mediterranean Diet and physical activity in Romanian and Spanish university students - a comparative study - G. Badicu; C.R. Chacón; F. Zurita-Ortega; M. Castro-Sanchez; L. Balint (Physical Education of Students, 2018)
Purpose: The main purpose of this research was to show if there are differences between the Mediterranean diet and physical activity in students from Romania and Spain. Material: The study was carried out on a sample of 567 participants, 149 of which (24.69%) are from Romania (Transilvania University of Braşov) and 427 (75.31%) are students from Spain (University of Granada ). To evaluate adherence to the Mediterranean diet we used The Mediterranean Diet Quality Index (KIDMED), and for the assessment of the level of physical activity, we used the Physical Activity Questionnaire for Adolescents (PAQ-A). The reliability of the KIDMED was good (Cronbach’s α = 0.83) and for PAQ-A is 0.874. Statistical analyses were done through program IBM SPSS Statistics 22. The statistical indicators used in this study, were the following: standard deviation (SD), arithmetic average (X), chi-square test, Student’s T-test (t), percent%, Levene’s test, ANOVA One-Way. Results: The results of the variance analysis showed that there is no statistically significant relationship between the adherence to the Mediterranean diet and physical activity in Romanian students (F=0.517; p=0.598), or in Spanish students (F=0.255; p=0.775). Also, the results regarding adherence to the MD and PA was: poor adherence , n=31, (mean=29.06; standard deviation=3.723), average adherence , n=275, (mean=28.62; standard deviation=3.386), and high adherence, n=261 (mean=28.50; standard deviation=3.779). Conclusions: This study highlighted the fact that there are no significant differences regarding the adherence to the Mediterranean diet and the level of physical activity between the two countries (Romania and Spain). Unlike Spanish students, we found that Romanian students have a poor adherence to the MD.